Ecophysiological responses of marine macroalgae to climate change factors - Ji, Yan; Xu, Zhiguang; Zou, Dinghui; Gao, Kunshan (Journal of applied phycology, 2016)
Marine macroalgae are ecologically and economically important primary producers, being adjacent to human living areas and playing key roles in coastal carbon cycles. They are subject to both regional and global environmental changes in coastal waters, where environmental factors fluctuate dramatically due to high biological production and land runoff. Since global ocean changes can influence coastal environments, global warming-induced ocean warming, ocean acidification (OA) caused by atmospheric CO 2 rise and increasing ultraviolet B (UVB) irradiance at the earth’s surface are affecting physiology, life cycles, and community structures of macroalgae. Here, we examine recent progress towards understanding the effects of these climate change factors on ecophysiology of macroalgae. Some species tested show enhanced growth and/or photosynthesis under elevated CO 2 levels or ocean acidification conditions, possibly due to increased availability of CO 2 in seawater with neglected influence of pH drop. Nevertheless, OA can harm some macroalgae due to their high sensitivity to the acidic perturbation to intracellular acid–base stability. Mild ocean warming has been shown to benefit most macroalgae examined. Respiration quotient increased due to combined effects of ocean warming and acidification. UVB almost always harms the physiological functions of macroalgae, which develop protective strategies, such as accumulation of UV-absorbing compounds; UVA can drive photosynthesis under moderate levels of solar radiation or when solely exposed to it. However, little has been documented on the interactions of these multiple stressors. Future work requires further investigations to examine the effects of OA under complex environments or under multiple stressors to advance knowledge on macroalgal global change biology.